The nexus between global disruption due to the covid-19 and performance of the construction project - Jabeen, S.; Sheraz, F.; Haider, S. A.; Iqbald, S.; Jahan, S.; Tehseen, Shehnaz *; Hussaini, T. (Growing Science, 2021)
In the current COVID-19 pandemic, this paper attempts to empirically find out the increasing workplace bullying effect on project performance with employee deviant behaviour as a mediator, internal, and external locus of control as moderators. The random sampling technique was used to gather data from 777 employees, working in construction companies in Pakistan. The examination was established using WarpPLS software version 7.0. The results revealed that workplace bullying is positively associated with employee deviant behaviour which in return negatively affects the project performance. It can be inferred from the results that the “moderating role” of internal “locus of control” is insignificant; whereas the external “locus of control” significantly moderates the relationship between workplace bullying & employee deviant behaviour. The proposed research and hypotheses support social exchange theory and social behaviour exchanges. This study has clarified some unique points that are equally important for the managers, employees, and project-based construction organization as a whole. It is also recommended that once the pandemic COVID-19 passes, it would be the dire need of that time to re-evaluate that, what has been changed in terms of professional thinking, working & behaving as for as their project work and communication between the team members is concerned.